2012
DOI: 10.4308/hjb.19.4.191
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Fish in the Upper Citarum River: an Adaptive Response to Physico-Chemical Properties

Abstract: Distribution of fish in river is controlled by physico-chemical properties of the water which is affected by land-use complexity and intensity of human intervention.A study on fish distribution was carried out in the upper Citarum River to map the effects of physio-chemical properties on habitat use. A survey was conducted to collect fish and to measure the water quality both on dry and rainy season. The result showed that distribution of the fish, in general, represented their adaptive response to physico-che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Although pyrethroids are considered to be slightly toxic to mammals and birds, they exhibit high acute and chronic toxicity in aquatic organisms [10]. Several studies have demonstrated that the Upper Citarum River is home to aquatic organisms from the lowest to the highest trophic levels, including algae of the family Bacillariophyceae, planktonic crustaceans such as Daphnia sp., and 10 species of fish [48][49][50]. Toxicological properties of permethrin and deltamethrin in some of these species are presented in Table 2.…”
Section: Risk Assessmentmentioning
confidence: 99%
“…Although pyrethroids are considered to be slightly toxic to mammals and birds, they exhibit high acute and chronic toxicity in aquatic organisms [10]. Several studies have demonstrated that the Upper Citarum River is home to aquatic organisms from the lowest to the highest trophic levels, including algae of the family Bacillariophyceae, planktonic crustaceans such as Daphnia sp., and 10 species of fish [48][49][50]. Toxicological properties of permethrin and deltamethrin in some of these species are presented in Table 2.…”
Section: Risk Assessmentmentioning
confidence: 99%
“…The Citarum River in West Java, Indonesia, covers an area of approximately 13,000 square kilometres, and is of vital importance to the water supply of both the Bandung and greater Jakarta metropolitan areas. Almost 10 million people reside in Bandung, with a further 25 million in greater Jakarta (Sunardi et al, 2012;Halpern et al, 2015;Borgwardt et al, 2019). The Citarum River provides as much as 80% of the surface water regulated by Jakarta's water supply authority, irrigates farms supplying 5% of Indonesia's rice, and is a source of water for upwards of 2,000 factories (World Water Week, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the global health of aquatic ecosystems is under extreme pressure from a wide range of anthropogenic contaminants, including pollutants derived from agricultural, mining, domestic, and industrial sources (Borgwardt et al, 2019;Halpern et al, 2015;Sunardi et al, 2012). The Citarum River is also experiencing severe water pollution and has been ranked among the most polluted rivers in the world (Cavelle, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The designation of the Citarum River is divided by region. Upper watershed is still dominated with natural forest, tea, and for the middle water shed is dominated Village, Vegetable Garden, Paddy Field, and the lower watershed is dominated with industries [8].…”
Section: Introductionmentioning
confidence: 99%